2022
DOI: 10.1155/2022/7688109
|View full text |Cite
|
Sign up to set email alerts
|

Application of Wireless Sensor Network Technology Using Intelligent Algorithm in Mismatch Detection of Photovoltaic Power Generation

Abstract: The paper was aimed at ensuring the stable operation of the photovoltaic power generation system (PVPGS) and improving the accuracy of automatic mismatch detection. Consequently, this paper presents a PVPGS-oriented mismatch detection system based on wireless sensing technology (WSN). Firstly, the photovoltaic array (PVA) is constructed using a microcontroller, power management chip, nRF24L01, temperature sensor, voltage, and current sensor. Then, a fault detection and localization (FDL) scheme based on the Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The experimental results showed that the ANFIS model improved power point tracking ability and reduced energy loss. On the other hand, Xie et al [ 25 ] investigated a PVM-oriented mismatch detection system using wireless sensing technology and achieved 100% accuracy in detecting array aging, shadow, and open circuit faults. Iqbal et al [ 26 ] proposed a grid-connected PV plant with a rated power of 125 kWp to compare actual performance with theoretical results.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results showed that the ANFIS model improved power point tracking ability and reduced energy loss. On the other hand, Xie et al [ 25 ] investigated a PVM-oriented mismatch detection system using wireless sensing technology and achieved 100% accuracy in detecting array aging, shadow, and open circuit faults. Iqbal et al [ 26 ] proposed a grid-connected PV plant with a rated power of 125 kWp to compare actual performance with theoretical results.…”
Section: Introductionmentioning
confidence: 99%